USM, GUFS CHINA SIGN MOU TO ENHANCE COOPERATION IN THE STUDY OF MALAY-CHINESE LANGUAGES, TRANSLATION AND CULTURE - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
GUANGZHOU, CHINA, 13 May 2017 The Universiti Sains Malaysia (USM) School of Humanities (PPIK) has signed a Memorandum of Understanding (MoU) with the Malay Language Department, Faculty of Asian Languages and Culture (FALC), Guangdong University of Foreign Studies (GUFS) in Guangzhou, China.